Diskursus Perang Dalam Perspektif Islam - Hakiki, Kiki Muhamad; Kesuma, Arsyad Sobby; Muttaqien, Zaenal; Badruzaman, Badruzaman (AL-ADYAN, 2019)
This study focuses on the study of texts (Al-Qur'an and Hadith) about war, tracing history, and ending with a study of the types of warfare that are permitted in Islam. This research is based on library research, of course there are several methodological tools used to find answers; in collecting data, of course, it refers to the main sources namely Al-Qur'an and Hadith by applying the work patterns of the maudhu 'method, then it is equipped with references to interpretation and historical books. While in the analysis, researchers used the double movement theory Fazlur Rahman. In this study conclude that in the Islamic conception, the problem of war has been arranged comprehensively, both at the goal stage, the conditions for allowing war, to the ethics of war, have been described in detail. In principle, in Islam, war is only legalized in very emergency situations (forced), such as to resist enemy attacks, defend the rights that have been violated by the enemy, and protect the security of Islamic da'wah. Islam only justifies war if attacks do occur or are real.